Business resilience during crises: a comparative study between PN17 and 50 FTSE Bursa Malaysia KLCI constituent companies - Kontot, Keria; Chin, Wee Chien; Lim, Ai Ling (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This was an event study that employed a non-parametric analysis using STATA. Data from 50 companies listed under Bursa Malaysia (BM), which consist of 21 companies classified under PN17 and 36 companies from the constituents top 50 FTSE at BM, were collected for five years (2018-2022). Using the Altman Z-Score, PN17 and T50FTSE companies were clustered under safe, grey, and distress zones. Besides, the study also aimed to examine the roles of a robust risk management system in managing a crisis among PN17 and the top 50 FTSE companies. The survey results revealed the significance of having an integrated and unified risk management for every company to ensure business continuity and resist crises. The study exposed the likelihood of managers manipulating the earnings figure during the pandemic and the significant positive relationship between the Operational Resiliency Framework (ORF) and Altman’s Z-Score. A less robust risk management system makes a corporation more likely to fall into the distress zone category.